Increasing Business Effectiveness Through The Implementation Of An Integrated Digital Marketing Strategy - Sayudin, Sayudin; Kartono, Kartono; Curatman, Aang (Riviera Publishing, 2023)
Information technology's evolution urges global businesses to adapt to the digital era, instigating changes in technology, customer interactions, and product/service marketing. Digital marketing strategies, particularly integrated ones involving social media, search engines, and paid campaigns, are crucial for sustained business success. This research explores how companies can boost performance through integrated digital marketing, emphasizing the correlation with increased brand awareness, market penetration, and customer loyalty. In response to the digital era's paradigm shift, where customers are highly connected online, the study investigates the integration of digital marketing elements (social media, SEO, PPC campaigns) to enhance overall business effectiveness. Employing literature analysis, case studies, and surveys with a quantitative approach, the research assesses the impact of these strategies on brand awareness, market penetration, and customer loyalty. Findings indicate a positive contribution to business growth through integrated digital marketing. Companies adept at optimizing digital channels through an integrated plan are poised for greater success in achieving marketing goals. The research concludes that an integrated digital marketing strategy is pivotal in enhancing business effectiveness in the digital age, offering valuable insights for practitioners, marketing managers, and researchers navigating intense digital competition towards larger business goals.